MANAJEMEN PERILAKU MELALUI PENGAMALAN SHOLAWAT WAHIDIYAH - Arif Sudaryana; Hibana (Jurnal Multidisipliner Bharasa, 2022)
Shalawat wahidiyah is a number of many teachings or practices that are based on Islamic sharia. This researcheraims to explain theimplementation of mujahadah shalawat wahidiyah as well as the benefits of wahidiyah shalawat for its practitioners. This research is qualitative research with a takaan or normative approach. Data collection techniques through library studies. The results showed that wahidiyah shalawat is a practical guidance born in carrying out the guidance of the Prophet, which includes sharia, essence, faith, Islam, ihsan, and moral / moral. Shalawat wahidiyah emphasizes on the side of human awareness of the presence of Allah and His Messenger. This awareness is what further makes the practitioner realize his condition and position before Allah as a creature full of sins and errors, and then say a prayer of supplication (forgiveness of sins, shafa'at of the Prophet, and others). It is self-awareness and confession that ultimately makes the practitioner feel the peace of heart and mind.